Treasury Reform in Kazakhstan : Lessons for Other Countries - Tandberg, Eivind (IMF Working Papers; Working Paper ;, 2002)
Kazakhstan's government has established a comprehensive and efficient treasury system for government revenues and expenditures, and introduced a state-of-the-art government financial management information system. Kazakhstan is among the leading BRO (Baltics, Russia, and other Former Soviet Union) countries in modernizing its budget execution system despite remaining challenges in other areas of fiscal management. The successful outcomes are related partly to the high quality of the reform process, and partly to the institutional design of the Kazakh treasury. Some design features are common for most well-functioning treasuries. Other features are related to the specific economic factors, institutional features, and financial management objectives of a transition economy, with a strong emphasis on fiscal control and financial discipline.